A paper-based electrode using a graphene dot/PEDOT:PSS composite for flexible solar cells - Lee, Chuan-Pei; Lai, Kun-Yu; Lin, Chin-An; Li, Chun-Ting; Ho, Kuo-Chuan; Wu, Chih-I; Lau, Shu-Ping; He, Jr-Hau (Nano energy, 2017)
We have synthesized a metal-free composite ink that contains graphene dots (GDs) and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) that can be used on paper to serve as the counter electrode in a flexible dye-sensitized solar cell (DSSC). This paper-based GD/PEDOT:PSS electrode is low-cost, light-weight, flexible, environmentally friendly, and easy to cut and process for device fabrication. We determined the GD/PEDOT:PSS composite effectively fills the dense micro-pores in the paper substrate, which leads to improved carrier transport in the electrode and a 3-fold enhanced cell efficiency as compared to the paper electrode made with sputtered Pt. Moreover, the DSSC with the paper electrode featuring the GD/PEDOT:PSS composite did not fail in photovoltaic tests even after bending the electrode 150 times, whereas the device made with the Pt-based paper electrode decreased in efficiency by 45% after such manipulation. These exceptional properties make the metal-free GD/PEDOT:PSS composite ink a promising electrode material for a wide variety of flexible electronic applications. [Display omitted] •Water–soluble GDs and PEDOT:PSS are used for preparing Pt–free counter electrode.•GD/PEDOT:PSS–coated paper electrode exhibits higher performance than that with the paper with sputtered Pt.•GD/PEDOT:PSS–coated paper electrode shows unfailing performance after 150 bending cycles.•GD/PEDOT:PSS–coated paper electrode is low–cost, light–weight, and environmental friendly.